An analysis of distant metastasis cases from HPV-associated oropharyngeal squamous cell carcinoma. Issue 4 (April 2021) - Brkic, Faris F.; Kadletz-Wanke, Lorenz; Kenner, Lukas; Füreder, Thorsten; Jank, Bernhard; Brunner, Markus; Heiduschka, Gregor
Abstract: Although mostly associated with good survival outcomes, some patients with HPV-positive oropharyngeal squamous cell carcinoma develop distant metastasis and face dire prognosis. The aim of this study was to analyze distant metastatic patients in regards to survival, clinical staging, therapy approach and p16/HPV status. This retrospective single-centre study assessed patients with HPV-associated oropharyngeal cancer with distant metastasis treated in a tertiary referral center from 2005 to 2019. Overall- (OS) and survival after diagnosis of distant metastasis (OMS), clinical staging and different therapy approaches were assessed. Moreover, the overall mortality was assessed, as well as the association of different therapy approaches and p16/HPV status with the survival outcome. Out of 211 patients with HPV-associated oropharyngeal cancer that were treated in the study period, 15 developed distant metastases (7.1%). Median OS and OMS of the total group were 11 months (range 0.1–32 months) and 3 months (range 0.1–21 months), respectively. The overall mortality rate was 53.3% (n = 8). Significantly better outcome was present in patients treated with primary chemoradiotherapy (median OS 17 months vs. not reached, p  = .03, median OMS 8 months vs not reached, p  = .05). The OMS was significantly better in patients treated with chemotherapy initially after diagnosis (mean OMS 21 months vs 4 months; P = .001). Surgical resection after initial diagnosis was associated with a significantly shorter OMS (median OMS 3 vs. 21 months, p  = .005). Interestingly, postoperative adjuvant therapy was delayed in all of these cases due to surgical site complications. Systemic treatment after initial diagnosis may be beneficial in clinical outcome of HPV associated distant metastases. Furthermore, surgical site complications should be treated with immediate care in order to avoid delay of adjuvant therapy. Further studies are warranted for validation of our results.